2008
DOI: 10.1111/j.1365-2702.2008.02373.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of nurse communication with patients with complex communication needs with a focus on the use of augmentative and alternative communication

Abstract: Communication with all patients is very important to the provision of quality nursing care. Communication cannot always be achieved using the speech modality. Nurses need to have tools and skills that will allow them to communicate with all of their patients whether or not they can speak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
161
0
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(174 citation statements)
references
References 34 publications
2
161
0
11
Order By: Relevance
“…Although communication with patients receiving mechanical ventilation is challenging for patients, nursing staff, and patients' families, certain communication behaviors and methods alleviate these difficulties 22,23 and reduce patients' distress. 12 Such methods include lip reading, use of pen and paper, 9 positive body language, friendly facial expression, eye contact and yes-no questions, 12,24 clicking the tongue or using a bell or clicking device, 25 and even touch.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although communication with patients receiving mechanical ventilation is challenging for patients, nursing staff, and patients' families, certain communication behaviors and methods alleviate these difficulties 22,23 and reduce patients' distress. 12 Such methods include lip reading, use of pen and paper, 9 positive body language, friendly facial expression, eye contact and yes-no questions, 12,24 clicking the tongue or using a bell or clicking device, 25 and even touch.…”
mentioning
confidence: 99%
“…26 Other low-technology devices that may be helpful include word or picture charts, alphabet boards, and erasable boards. 4,18,23 More advanced technological devices, such as communication aids that rely on computerized electronic voice output, are generally used on the basis of individual patient assessment and evaluation for longer term patients receiving mechanical ventilation. 2 Additional methods that enable patients to speak are invasive modified speech approaches for patients on permanent respirator support and a Portex Vocalaid (a fenestrated endotracheal tube) for patients who require a constantly inflated tube cuff.…”
mentioning
confidence: 99%
“…Many studies have reported time as an important obstacle to education and have demonstrated that time is should be increased to establish communication (20,28,29). Another study reported lack of intra-and intersectoral cooperation, absence of monitoring and evaluation programs, lack of conspicuous administrative regulations, lack of health education priority by policymakers and positive attitude towards it, insufficient attention to the trainers' feedbacks, and achievements as barriers to health education (30).…”
Section: Discussionmentioning
confidence: 99%
“…Iz toga možemo zaključiti da sestre imaju premalo znanja o komunikaciji, krivo tumače upute nadređenih, podcjenjuju važnost informacija za pacijenta i kao rezultat toga pacijentu prenose nedovoljno važnih informacija o njegovu zdravstvenom stanju i sl. 21 Različiti autori navode savjete za uspješnu komunikaciju medicinske sestre s pacijentom: upotrebljavajte literatura Većina ispitanika (88 %) rješava sukobe mirnim razgovorom, 50 % smatra ispriku vrlo važnom, a 45 % sukobe rješava podizanjem glasa. Za njih možemo reći da su naporni pacijenti koje medicinska sestra mora naučiti svladavati s pomoću svojeg stabilnog položaja, pravim pristupom i poznavanjem vještina rada s napornim pacijentima 28 .…”
Section: Raspravaunclassified